ANALISIS PENGGUNAAN PADA EFISIENSI TRANSAKSI KEUANGAN PADA UMKM DI BOEPINANG - Ardinal, Ardinal; Turi, La Ode; Syahrir, Sasmita Nabila (Jurnal Akuntansi Kompetif, 2025)
This study aims to analyze the use of QRIS in enhancing the efficiency of financial transactions among MSMEs in Boepinang, identify the supporting and inhibiting factors of its adoption, and examine its impact on business profits. QRIS (Quick Response Code Indonesian Standard) is an electronic payment system developed by Bank Indonesia, which enables transactions via QR codes. For regular merchants, a Merchant Discount Rate (MDR) of 0.7% is applied per successful transaction. This research employs a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The data were analyzed using data reduction, data display, and conclusion drawing techniques. The results indicate that QRIS significantly improves operational efficiency for MSME actors, offering faster transactions, automatic recording, and ease of payment. The main supporting factor is its user-friendly operation via smartphones. However, key obstacles include unstable internet connectivity and transaction fees borne by business owners. Regarding profitability, QRIS adoption has not resulted in a notable increase or decrease in profits. Nonetheless, it positively contributes to operational efficiency and transaction management within MSMEs. Keywords: Efficiency, QRIS, MSMEs, financial transactions, profit